Efeito do Diodo Emissor de Luz (LED) sobre lesões causadas por veneno de serpentes do gênero Bothrops em células musculares esqueléticas C2C12 - Santos, Adriano Silvio dos (2018)
The venom of the snakes of the Bothrops genus, induces an intense local inflammatory reaction, characterized by pain, edema and leukocyte migration, this process can results in tissue necrosis of the affected limb. The use of antibotrope serum has the function to neutralize a greater amount of circulating venom as possible, reducing systemic effects, but its action does not extend to local manifestations. The objective of this work was to analyze the effect of LED on C2C12 muscle cells submitted to injury by venom of snakes B. jararacussu and B. moojeni regarding cell integrity and viability. After the incubation period, the cells received the venom of Bothrops jararacussu snakes and Bothrops moojeni, at concentrations of 5, 10, 12.5, 25.50 and 75 μg / mL and were immediately irradiated with LEDs, at the wavelength (λ) of 636nm, energy density 4J / cm2, potency 160 mW , total energy 11.2J, irradiation time 70 seconds and incubated for 30, 60 and 120 min. The results showed that venom of B. jararacussu and B. moojeni snakes affected the integrity of the cells in a dose-time dependent manner. The LED was able to protect the cellular integrity against the venom of B. jararacussu at 120 min at concentrations of 5, 10, 12.5, 25 and 50 μg / mL. The same protective effect was observed in 60 minutes at concentrations of 12.5, 25, 50 and 75 μg / mL and at 120 minutes at 25 μg / mL after addition of B. moojeni venom. The venom of B. jararacussu decreased cell viability at all times analyzed. The LED was not able to revert the effects of venom at 30 and 120 min, but in 60 min showed a significant increase in cell viability at concentrations of 50 and 75 μg / mL. B. moojeni venom was able to decrease cell viability at all concentrations and times established. The LED was not able to revert this frame at the 30 and 60 min times, but at 120 min the LED was able to increase cell viability at the concentration of 50 μg / mL. Therefore, these results suggest that the LED protects against cellular integrity.